The cytological features of mammary analogue secretory carcinoma: A series of 6 molecularly confirmed cases. Issue 5 (5th December 2012) - Griffith, Christopher C.; Stelow, Edward B.; Saqi, Anjali; Khalbuss, Walid E.; Schneider, Frank; Chiosea, Simion I.; Seethala, Raja R.
Abstract : BACKGROUND: Mammary analogue secretory carcinoma (MASC) of the salivary glands is a newly described tumor entity associated with the t(12;15)(p13;q25) ETV6‐NTRK3 translocation. Early studies have shown this tumor to be a distinct entity with histologic, biologic, and clinical differences from acinic cell carcinoma and adenocarcinoma, not otherwise specified. Because this tumor was described only recently, it remains relatively unknown outside of head and neck specialty pathology centers. METHODS: In the current study, 6 cases of fine‐needle aspiration cytology from histologically and/or molecularly confirmed cases of MASC are presented. RESULTS: Using cytomorphology, MASC primarily raises the differential diagnosis of an oncocytic salivary gland tumor but there are some features that can suggest the specific diagnosis of MASC. The 6 cases presented in the current study all demonstrated at least focal cytoplasmic vacuolization and papillary formations on smears. MASC can be differentiated from acinic cell carcinoma by a lack of periodic acid‐Schiff diastase–positive zymogen granules and S‐100 protein positivity. CONCLUSIONS: The results of the current study the ability of ETV6 break‐apart fluorescence in situ hybridization to detect gene rearrangement on cell block material. This is the first report of a case of MASC prospectively diagnosed on a cytology specimen. Cancer (Cancer Cytopathol) 2013;121:234–41. © 2012 American Cancer Society.